Diagnositic value of serum bile acid estimations in liver disease. Issue 6 (June 1975) - Barnes, S; Gallo, G A; Trash, D B; Morris, J S
Abstract : Bile acid concentrations were estimated enzymatically in fasting and postprandial (two-hour) serum samples from 18 normal subjects and 30 patients with histologically proven hepatobiliary disease. The serum bile acid concentration was less than 15 mumol/1 in normal subjects and did not increase postprandially. The fasting serum bile acid concentration was raised in 27 of the patients with hepatobiliary disease, and following a meal was outside the normal range in all 30 patients. Other liver function tests were abnormal less frequently. These results suggest that the estimation of serum bile acids in the postprandial state is a sensitive screening test of hepatobiliary disease. They should be of particular value in patients in whom liver disease is suspected but not proven, and in those recovering from liver disease, especially following therapy.